THE DEVELOPMENT OF VERBAL INTELLIGENCE OF A TEACHER IN THE POSTGRADUATE EDUKATION - Сафарян, Світлана (Modern engineering and innovative technologies, 2023)
one of the main tasks of modern school literary education is the formation of students’ reading competence, which is impossible without a developed reader’s perception of works of art based on the artistic thinking of the recipients. The article is devote